Penile cancer – Guideline adherence produces optimum results. Issue 4 (August 2015) - Breen, K.J.; O'Connor, K.M.; Power, D.G.; Mayer, N.J.; Rogers, E.; Sweeney, P.
Abstract Objective To audit the management and outcome of penile cancer in a tertiary university teaching hospital, comparing our results to international best practice and published guidelines. Methods The Hospital Inpatient Enquiry database of the Mercy University Hospital was interrogated for penile cancer patients treated between 2001 and 2012. Data relating to presentation, local treatment, histology, lymph-node management, outcome and survival was recorded. Data were analysed using the Log Rank test, with significance defined as P ≤ 0.05. Results Twenty-five patients were identified with a median age of 61 years. The majority of cases at presentation were ≥T2 (54%) and intermediate to high grade (76%). The median follow-up of patients was 3.75 years (range 9 months–10 years). Overall survival was 76% (n = 19), these patients are all disease free to date. Disease-specific survival was 85% at 10 years. Penile cancer related mortality was 8% (n = 2), 4 patients (16%) died of non-penile cancer related causes. Twenty-two patients (88%) had surgery and 3 patients (12%) had radiotherapy. Based on EAU guidelines inguinal lymph node dissection (ILND) was performed in 64% (n = 16) of cases with 44% (n = 7) of these patients requiring concurrent bilateral pelvic lymph node dissection. Fifty percent (n = 8) of ILNDs showed metastatic disease. Ten year disease-specific survival for node negative versus node positive disease is 100% versus 57%. Thirty-two percent (n = 8) of patients received chemotherapy. Conclusions Penile cancer is a rare oncological condition that often requires bilateral inguinal ± pelvic lymph node dissection and should be managed according to published guidelines, in specialist centres in order to maximize outcomes.